Diagnostic validity of blunt abdominal trauma scoring system (BATSS) on blunt adominal trauma in Sanglah General Hospital, Denpasar, Bali - Adityas Sukmadi Karjosukarso; I Ketut Wiargitha; Tjokorda Gde Bagus Mahadewa; Nova Juwita (Indoscholar, 2019)
Background: Abdominal trauma is the third leading cause of death in trauma patients and can be found in about 7-10% of the total number of trauma cases. The Blunt Abdominal Trauma Scoring System (BATSS) provides a high-accuracy score system for diagnosing injury to intra-abdominal organs in blunt abdominal trauma patients based on clinical features, such as patient history, physical examination, and Focused Assesment with Sonography for Trauma (FAST). This studyaimed to determine the validity of the diagnostic value of BATSS score in cases of blunt abdominal trauma. Method: This research was conducted at Sanglah General Hospital, Denpasar with a total sample of 44 patients. The subjects were abdominal blunt trauma patients who meet the inclusion and exclusion criteria. This study was a retrospective study to determined the validity of the BATSS score. Result: Of the 44 patients, BATSS score ≥12 was found at 34 (77.3%) and BATTS <12 scores of 10 (22.7%). For groups with BATSS score ≥12, there were 32 (94.11%) patients. As for the group with BATSS score <12, there were 3 (30%) patients with organ rupture. A validity test of BATSS score obtained showed 91.4% sensitivity, 77.77% specificity, positive predictive value 94.1%, negative predictive value 70%. Conclusion: BATSS can be a tool of early identification and stratification of patients at high risk of the occurrence of intra-abdominal organ injury due to blunt abdominal trauma.